(untitled) (The Agriculturists, 2014)
Genetic diversity of 40 traditional Bangladeshi rice genotypes was studied under rainfed condition through Mahalanobis D2 statistic for grain yield and yield contributing characters. The genotypes were grouped into six clusters. The inter-cluster distances were higher than intra-cluster distances indicating wider genetic diversity among the genotypes of different clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the clusters. The cluster VI contained the highest number of genotypes (18) and the clusters I and II contained the lowest (1). The highest intra-cluster distance was noticed for the cluster IV and lowest for cluster VI. The highest inter-cluster distance was observed between cluster I and IV, followed by cluster I and II, cluster I and III and the lowest between cluster III and IV. Regarding inter-cluster distance, the genotypes of cluster IV showed high genetic distance from all other clusters. The genotypes from cluster IV could be hybridized with the genotypes of other clusters for producing transgressive segregants. Based on canonical vector analysis, panicle number per plant and 1000 grain weight had maximum contribution towards genetic divergence. The highest cluster means for yield, filled grains panicle-1 and grain breadth were obtained from cluster VI. The highest means for plant height, flag leaf area, unfilled grains panicle-1, harvest index and the lowest growth duration were found in cluster I, while the lowest mean value for yield, grain length, 1000 grain weight, plant height and highest mean value for days to flowering and maturity were found in cluster II. The crosses between the genotypes/parents of cluster VI and cluster II, cluster VI and cluster V would exhibit high heterosis as well as higher level of yield potential. Therefore, more emphasis should be given for selection of the genotypes from clusters I, VI and V for future breeding program. DOI: http://dx.doi.org/10.3329/agric.v12i1.19576 The Agriculturists 2014; 12(1) 26-32